Lines for blast resistance genes with genetic background of Indica Group rice as international differential variety set - Fukuta, Yoshimichi; Koide, Yohei; Kobayashi, Nobuya; Kato, Hiroshi; Saito, Hiroki; Telebanco-Yanoria, Mary Jeanie; Ebron, Leodegario A.; Mercado-Escueta, Doris; Tsunematsu, Hiroshi; Ando, Ikuo; Fujita, Daisuke; Obara, Mitsuhiro; et al. (Wiley, 2022)
Twenty‐one near‐isogenic lines (NILs) for 18 resistance genes—Pia,Pii,Pi3,Pi5(t),Pik‐s(two lines from two donors),Pik‐m,Pi1,Pik‐h,Pik,Pik‐p,Pi7(t),Pi9(t),Piz,Piz‐5,Piz‐t,Pita‐2,Pita(three donors) andPi20(t)—to blast disease were developed through introduction into the genetic background of a semi‐dwarf susceptible rice line, US‐2, by recurrent backcross breeding. US‐2 is derived from a cross between an Indonesian Tropical Japonica Group cultivar, 'Kencana', and an improved high‐yielding and semi‐dwarf Indica Group cultivar, 'Takanari', bred in Japan. The reactions of US‐2 NILs to standard differential blast isolates were clearly defined than previous differential varieties (DVs) such as monogenic lines. US‐2 and its NILs are adapted well to wide environmental conditions from temperate to subtropical regions. They will be useful and easier to handle and manage as the first DV set with genetic background of Indica Group rice for pathology studies and as gene sources for rice breeding programme.